Quantile-VaR is the wrong measure to quantify market risk for regulatory purposes - Stefan R. Jaschke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
Starting from the objective of banking supervision - to minimize the overall costs of banking to the general public - we show that the current standard of quantifying market risk is flawed. It is perfectly aligned with the interests of banks' shareholders and management, but not with the interests of the general public. This is unsatisfactory from a normative point of view, as significant public resources are used for banking supervision.
urn:nbn:de:kobv:11-10050093
Keywords: K2; G2; 330; VaR; banking regulation; supervision; risk measures; Basel Accord